Perancangan Fasilitas Komunitas Kristen Di Pekanbaru Dengan Pendekatan Arsitektur Simbolik - Yohanes Sitorus; Yohannes Firzal; Ratna Amanati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The development of the Christian is basically not detached from some roles of the Church's youth as the next generation. In developing nations which have various crises, the role of youth with great spiritual, intelligent, and morality quality is required. With the rapid growth of Christian population in Pekanbaru, a means known as Christian community facility is needed to motivate the Christians, especially the youths in order to realise the great potential in themselves. This facility is meant to be centre of icon for the youths in conducting spiritual guidance. To maintain christianity values, this Christian facility will be designed using symbolic architectural approach which applies Eikumene philosophy in its design concept. Those symbol and principle will make atmosphere in the design stronger with Christian spirituality nuance. Christian spirituality nuance applied on orientation, symbol, aperture, colors, sound and vegetation.Keyword: Christian, Eikumene, Symbolic Architecture.